Reactualization of Pancasila's Value of Justice in the Perspective of Quranic Interpretation of Justice - Muh Rafli (Jurnal El-Thawalib, 2026)
Justice is one of the fundamental values in the philosophical foundation of the Indonesian state, namely Pancasila, especially in the principle of social justice for all Indonesian people. However, in contemporary social and political reality, there is still often a gap between the ideal value of justice and its practice in community life. In this context, the Qur'an, as the main source of Islamic teachings, provides a comprehensive ethical framework for the concepts of justice (al-'adl and al-qisṭ), emphasizing principles of balance, honesty, and the protection of human dignity. This study aims to analyze the reactualization of the value of justice in Pancasila through the lens of Qur'anic interpretation, with the aim of strengthening its moral and philosophical relevance in the life of the nation and state in Indonesia. This study uses a normative approach and a thematic interpretation method (tafsir maudhu'i) to analyze Qur'anic verses related to justice, with primary data from the Qur'an, Pancasila, and the 1945 Constitution, and secondary data from scientific articles, non-formal sources, and other documents. Data were collected using documentation methods and analyzed using content analysis. The results of the study indicate that the concept of justice in the Qur'an emphasizes impartiality, moral responsibility, and the obligation to uphold justice even against oneself or certain groups. These principles closely align with the Pancasila value of justice. Therefore, the reactualization of the values of justice in Pancasila through the lens of Qur'anic interpretation can strengthen ethical governance practices, promote social equality, and realize a just and equitable society in Indonesia. Word count: ±190.